(untitled) (Journal of Architectural Design, 2022)
The article deals with the optimization of the urban environment by means of landscape design. This problem can be solved through the use of various natural resources, one of which is plants. Plants play an important role in creating a favorable microclimate, creating a unified composition of any space, whether it is an urban landscape, public parks or specialized parks, as well as interiors.